PARTISIPASI SUBAK DAN PEMERINTAH TERHADAP OPERASI DAN PEMELIHARAAN PASCA PEMBANGUNAN INFRASTRUKTUR DISIMP II PADA DAERAH IRIGASI GADON DAS SUNGI DI KABUPATEN TABANAN - Wayan Yuliartha; I Nyoman Norken; Kadek Diana Harmayani (JURNAL SPEKTRAN, 2018)
lack of Subakparticipation as a water user farmer association (P3A) and the Government of the Operation and Maintenance of the irrigation network which resulted in disruption of the network as a whole. In line with this, one of the activities to be carried out is the rehabilitation of Irrigation network in the River Basin of Empas-Sungi especially in GadonIrrigation Area in Tabanan on the activities of DISIMP II (Decentralized Irrigation System Improvement Project in Eastern Region of Indonesia Phase II), which aims to restore and improve the functions of network facilities and irrigation.The study was conducted on Gadon D.I Watershed of SungiRiver with explorative methods, that is, studying and evaluating DI Gadon on the Watershed of Sungi River, by conducting interviews with members of Subak and relevant agencies. 73 respondents were selected based on purposive sampling method to measure attitudes, opinions and perceptions of Subak and the Government using Likert scale. Data were analyzed using descriptive qualitative methods and Linear regression to determine the role of water control system and the government against the post-construction operation and maintenance of infrastructure of DISIMP II in Gadonirrigated areas in the watershed of Sungi River in Tabanan Regency.Regression analysis showed that the Government had shown a greater role withthe beta standardizedcoefficient value of 0.499 (49.9%), followed by the role of Subak / P3A amounting to 0.344 or 34.4% of the Operations and Maintenance while 15.7% was influenced by factors that had not been included in this study. In this study, Subak / P3A had the participation or role lower than the participation of the government. The results also showed that the increase in government participation and Subakwill improve the operation and maintenance of the irrigation network of post Infrastructure Development of DISIMP II either partially or simultaneously. Keywords: Participation, SubakGadon, Government, Operations and Maintenance.